المسرح الجزائري و دوره في الحركة الوطنية الجزائرية و الثورة التحريرية (1926-1962) - بن العربي هجيرة; د/ جفال عمر (جامعة عمار ثليجي الاغواط, 2024)
الملخص بالعربية: لعب المسرح الجزائري دورا هاما في مقاومة الاستعمار الفرنسي باعتباره أحد روافد الحركة الوطنية ساهم في توعية الشعب الجزائري، وإعداده للثورة، وتهيئة الظروف المناسبة لقيامها هذا التوجه الوطني للمسرح ظهر منذ البدايات الأولى للنشاط المسرحي في أشكاله البدائية في القرن التاسع عشر، والذي سيتبلور بشكل واضح، ويتأكد بعد تأسيسه سنة 1926م كنوع أدبي و فني له أصوله وقواعده المتعارف عليها حديثا، لقد اندمج المسرح الجزائري في العمل الوطني، وظهرت العديد من الفرق المسرحية والمسرحيين الذين أبدعوا أعمالا درامية تنتقد السياسة الاستعمارية، وتعالج مختلف مشاكل وقضايا المجتمع الجزائري. الكلمات المفتاحية: المسرح، الحركة الوطنية، القضية الوطنية، الثورة الجزائرية. Abstract : The Algerian theatre played an important role in resisting French colonialism as a tributary of the patriotic movement that contributed to the Algerian people's awareness. and the preparation of the revolution, and the creation of conditions conducive to this national orientation of the theatre emerged from the earliest beginnings of theatrical activity in its primitive forms in the nineteenth century which will be clearly crystallized and confirmed after its founding in 1926 as a literary and artistic genre with its newly recognized origins and rules Algerian theatre has been integrated into national action, and many theatrical and theatrical groups have emerged, creating dramas critical of colonial politics and addressing the various problems and issues of Algerian society. Keywords: Theatre, National Movement, National Cause, Algerian Revolution.